Lech kocha Głupią Ludmiłę. Polacy i stereotypy słowiańskości a "Malowany ptak" Jerzego Kosińskiego - Hannan, Kevin (Er(r)go. Teoria - Literatura - Kultura, 2005)
Kevin Hannan Le(c)h Loves Stupid Ludmila: Poles, Slav Stereotypes and Jerzy Kosinski’s The Painted Bird The essay examines Jerzy Kosiński’s novel The Painted Bird in the context of the author’s biography (Kosiński’s war-time experiences) and its diverse receptions in Poland and the United States. The ideologies of Political Correctness and multiculturalism have prevented American scholars and the public from relating to the Polish perspective on the book and the events it purports to represent. In conclusion to his analysis, Kevin Hannan states: „The Painted Bird suggests a deceptive distortion of Polish history in the twentieth century, and the book demeans those Poles who risked their lives to save and shelter Jews such as Jerzy Kosiński”.